2017
DOI: 10.1002/ajmg.a.38415
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense variant in the GLI3 zinc finger domain in a family with digital anomalies

Abstract: Mutations in GLI3, which encodes a transcription factor of the Hedgehog signaling pathway, cause several developmental anomalies linked to inappropriate tissue patterning. Here, we report a novel missense variant in the fifth zinc finger domain of GLI3 (c.1826G>A; p.(Cys609Tyr)) initially identified in a proband with preaxial polydactyly type IV, developmental delay, sensorineural hearing loss, skeletal, and genitourinary anomalies. Additional family members exhibited various digital anomalies such as preaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…GLI3 c.1802A>G (p.His601Arg), a variant also situated within the zinc finger domain of GLI3, has been detected in 14 individuals with variable polydactyly‐syndactyly complex in a large Jewish Moroccan family with 4 generations (Volodarsky et al., 2014 ). Other research revealed GLI3 c.1826G>A; p.Cys609Tyr, another variant in the zinc finger domain, was associated with digital and skeleton anomalies by exhibiting diminished transcriptional activation capacity and inhibited expression of Hedgehog target genes regulated by additional GLI proteins (Crapster et al., 2017 ). Substantial evidence suggests that the gene sequence within the zinc finger protein region of the GLI3 gene plays an indispensable role in embryonic development, shaping the hands and feet.…”
Section: Discussionmentioning
confidence: 99%
“…GLI3 c.1802A>G (p.His601Arg), a variant also situated within the zinc finger domain of GLI3, has been detected in 14 individuals with variable polydactyly‐syndactyly complex in a large Jewish Moroccan family with 4 generations (Volodarsky et al., 2014 ). Other research revealed GLI3 c.1826G>A; p.Cys609Tyr, another variant in the zinc finger domain, was associated with digital and skeleton anomalies by exhibiting diminished transcriptional activation capacity and inhibited expression of Hedgehog target genes regulated by additional GLI proteins (Crapster et al., 2017 ). Substantial evidence suggests that the gene sequence within the zinc finger protein region of the GLI3 gene plays an indispensable role in embryonic development, shaping the hands and feet.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GLI1 , variants segregating with dominant nonsyndromic A/B‐type PAP were recently reported, and all the missense variants (6 in all) were in the Zn‐fingers of GLI1 (Palencia‐Campos et al, 2020; Yousaf et al, 2020). Variable digital and other abnormalities in a large family segregated with a missense GLI3 variant Cys609Tyr in Zn‐finger number 5 (Crapster et al, 2017), and the same Zn‐finger was affected in a four‐generation family with Greig cephalopolysyndactyly syndrome segregating with a GLI3 p.(Arg625Trp) variant (Debeer et al, 2003). Missense variants outside the Zn‐finger domain of GLI3 can also be pathogenic, e.g., p.(Ala934Pro) (Elson et al, 2002), and like GLI2 , most reported pathogenic GLI3 LoF variants are also of the truncating type (Démurger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Manifestation of one or another syndrome depends on the mutation site in the gene. Pallister‐Hall syndrome is generally caused by truncating variants that are located in the middle third of the GLI3 and generate a constitutive repressor allele (Al‐Qattan, Shamseldin, Salih, & Alkuraya, ; Crapster, Hudgins, Chen, & Gomez‐Ospina, ; Johnston et al, ). At the same time, a greater spectrum of pathogenic variants located before 1998 nt and after 3481 nt of GLI3 cDNA cause loss of function and manifest in GCPS (Furniss, Critchley, Giele, & Wilkie, ; Johnston et al, ; Kalff‐Suske et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the ZFN is suggested to be critical for the GCPS phenotypic manifestation, because this domain is fundamentally important for gene transcription, translation, cytoskeleton organization, epithelial development, cell adhesion, protein folding, and chromatin remodeling during early development (Laity, Lee, & Wright, ). The ZFN, which is highly conserved between evolutionary distinct species, is especially important for limb development (Al‐Qattan et al, ; Crapster et al, ).…”
Section: Discussionmentioning
confidence: 99%